Teoría mimética y educación sexual. Contra los géneros en conflicto. - Reyero García, David (2020)
The paper analyzes the concept of gender and its implications for the theory of education. The human being is going through a mimetic process also in what refers to sexuality. On the one hand, gender theories understand any framework related to sexuality as a construction that we can put into dispute through political debate. Faced with such theories, models supported by binary sexuality and complementarity resist. Our goal is to offer arguments to defend the reasonableness of these models.